Yoga as a complementary therapy in neuropathic pain: A systematic review and meta-analysis of randomized controlled trials - Praag Bhardwaj; Navdeep Ahuja; Ashwin Parchani; Shiana Singh; Dilasha Sethi; Monika Pathania (Journal of Family Medicine and Primary Care, 2023)
Yoga is an ancient wisdom comprising a multitude of physical and mental practices that are aimed toward a state of optimum physical, mental, social, and spiritual health. Neuropathic pain (NP) is caused by a lesion or disease of the somatosensory nervous system that is often unresponsive to currently available modes of treatment, portending an inferior quality of life for patients. This systematic review and meta-analysis aim to investigate the effect and the potential role of yoga in NP syndromes. PubMed, Scopus, Elton Bryson Stephens Company (EBSCO), and Cochrane Library were screened for randomized controlled trials (RCTs) assessing the effects of yoga in patients on NP. Usual care, no treatment, or any active treatments were acceptable as control interventions. Primary outcome measures were objective or subjective assessment measures of pain intensity. For each outcome, standardized mean differences and 95% confidence intervals (CIs) were calculated. A total of four studies were included for qualitative synthesis. Meta-analysis of three studies revealed an overall effect (Z) in the favor of yoga as an intervention for NP, when compared to controls, although the effect was not statistically significant (three RCTs; Z = 1.10 [P = 0.27]; Heterogeneity: τ2 = 0.37; χ2 = 27.78, df = 2 [P < 0.00001]; I2 = 93%). This review divulged the overall favorable effect of yoga in NP, although it was not statistically significant. It highlights the promising role of yoga on pain intensity and quality of life in NP syndromes while showing that yoga has the advantage of being an inexpensive and easily accessible mode of therapy. Extensive research on the efficiency and safety of yoga must be conducted using robust RCTs with rigorous methodologies.